Mites associated with raspberry in Zamora and Los Reyes, Michoacán - Villalvazo-Valdovinos, Ricardo; Pamatz-Ángel, María Mayra; Lara-Chávez, Ma Blanca Nieves; Ávila-Val, Teresita del Carmen; Vargas-Sandoval, Margarita (Revista Mexicana de Ciencias Agrícolas, 2024)
Mexico ranks second in raspberry production and very little knowledge has been generated about the mites associated with this crop. In the present work, mites collected in the aerial part of raspberries produced in the municipalities of Zamora and Los Reyes de Salgado, Michoacán, Mexico from February 2018 to March 2019, were identified. In Los Reyes, 8 748 mites belonging to four families and nine species were recorded. The species found were Amblydromalus ca. congeae, Neoseiulus californicus, Phytoseiulus persimilis, Typhlodromips sp., Euseius mesembrinus, Euseius sp. (Phytoseiidae), Tetranychus ludeni (Tetranychidae), Tarsonemus sp. (Tarsonemidae), and Tyrophagus putrescentiae (Acaridae). A total of 4 253 adult specimens of two species were collected in Zamora, Neoseiulus fallacis with 235 (Phytoseiidae) and Tetranychus ludeni with 4 018 (Tetranychidae).